2020
DOI: 10.3390/ijerph17239029
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Effects of the Health Promotion Programme “Join the Healthy Boat” on Objectively Assessed Sedentary Time in Primary School Children in Germany

Abstract: Sedentary behaviour (SB) in children is related to negative health consequences that can track into adulthood. The programme “Join the Healthy Boat” promotes reduced screen time and a less sedentary lifestyle in schoolchildren. This study investigated the effects of the programme on children’s SB. For one year, teachers delivered the programme. A total of 231 children (7.0 ± 0.6 years) participated in the cluster-randomised study; there were 154 one year later at follow-up. Children’s SB was assessed using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…As seen in the study [23], motivation of the teaching staff is not enough to achieve beneficial changes with the programs. Similarly, it was observed in the study [26], whose program did not work due to the low participation of families from home. Low family participation conditions the results [29].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As seen in the study [23], motivation of the teaching staff is not enough to achieve beneficial changes with the programs. Similarly, it was observed in the study [26], whose program did not work due to the low participation of families from home. Low family participation conditions the results [29].…”
Section: Discussionsupporting
confidence: 76%
“…The third and last study carried out in primary education [26], showed improvements in development and motivation towards physical activity or sports practice, however, this did not reduce the time dedicated to ICT consumption. In general terms, the program showed some changes, but it was not effective due to the scant participation and collaboration of families in controlling inappropriate habits.…”
Section: Effectiveness and Main Difficulties In The Development Of Programs That Promote Healthmentioning
confidence: 91%
See 1 more Smart Citation
“…Ten studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ] referred to published protocols [ 79 , 80 , 81 , 82 , 83 , 84 ] or trial registry records (trial IDs reported in Table 1 ) which were consulted in these cases. Nine studies [ 69 , 70 , 73 , 76 , 77 , 78 , 85 , 86 , 87 ] were judged to be of high risk of bias and four studies [ 71 , 72 , 74 , 75 ] to have some concerns. No studies were judged to be of low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…In two instances [ 88 , 89 ], the authors referred to an additional paper containing more detailed information on the respective study [ 90 , 91 ]. Of the 15 included studies, 14 studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 87 , 88 , 89 ] were published in peer-reviewed journals, 14 were written in English [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 87 , 88 , 89 ] and one [ 86 ] in German. The country of origin was Germany for 13 studies [ 69 , 70 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 85 , 86 , 87 , 88 ] and Belgium [ 89 ] and the UK [ 72 ] for one study each.…”
Section: Resultsmentioning
confidence: 99%